The effects of financial distress on financial performance: An empirical analysis of SMEs in Sheema, Buhweju, Rubirizi, and Bushenyi districts - Mpora, Eliab Byamukama; Bwengye, Anny Katabaazi; Atukunda, Emilly; Ngirababo, Rwusira Dan (African Journal of Business Management, 2025)
This study investigated the impact of financial distress on the performance of small and medium enterprises (SMEs) in Sheema, Buhweju, Rubirizi, and Bushenyi Districts, Uganda. Specifically, it examined the effects of excessive debt, inadequate capital, poor management practices, unwise expansion, intense competition, litigation, and unfavorable contracts on SMEs. Financial distress, if left unchecked, can lead to bank failures and severely harm the economy, emphasizing the need for close monitoring. This study aimed to determine the relationship between financial distress and SME performance. A descriptive research design was adopted, involving in-depth analysis of data collected from 180 respondents across the four districts. The findings revealed a significant negative correlation between financial distress and SME performance. As financial strain increased, financial performance declined, and vice versa. The study recommends that SMEs leverage technology to manage their financial records, ensuring ease of auditing and access to credit. Additionally, SMEs should employ skilled accountants for bookkeeping to enhance the quality of their financial records.